Investigation of Wadi Al-Shatti Iron Oxide Effects on the Gamma Ray Attenuation and Compression Strength of Hardened Concrete - Mohammed A. Al Madani; Yousef A. Abdullah; Elfitouri K. Ahmied; Noura S. Hawashi; Mahmoud J. Altayeb (Journal of Pure & Applied Sciences, 2022)
A local ore material from Wadi Al-Shatti (south west of Libya)  using different concentrations were investigated as a shielding material. The linear attenuation coefficients, mass attenuation coefficients and calculated density showed that the ore material used in this study may be preferred as shielding material against gamma radiation. It is clear from the results that as the sample thickness increases, the detector intensity decreases and when percentage of Wadi Al-Shatti Iron Oxide (WSIO) increases, the linear attenuation coefficient (LAC), on the other hand, the mass attenuation coefficients (MAC) decreased. Generally, the attenuation of WSIO increases as increasing the  linear attenuation coefficient.This research is also concerned with studying the  effect of replacing a mix sand of concrete with different weight of WSIO namely. It was expectedthat addition of iron oxide material with higher density higher hardness than Portland cement will increase the compressive strength. In general, the addition of low contents of WSIO to the concrete may improve the compressive strength, but still depends on the concentration of iron oxide as well as the thickness of the concrete.